ANALISIS KARAKTER TOKOH UTAMA DALAM NOVEL PASUNG JIWA KARYA OKKY MADASARI MELALUI PENDEKATAN PSIKOANALISIS SIGMUND FREUD - Wan Nurul Atikah Nasution; Eva Mizkat (Smart Education, 2025)
Abstract: In the field of Indonesian Language Education, it focuses on language and literature. This study examines literature which aims to: (1) Describe the Id of the Sasana character in the novel Pasung Jiwa by Okky Madasari? (2) Describe the ego of the Sasana character in the novel Pasung Jiwa by Okky Madasari? (3) Describe the superego of the Sasana character in the novel Pasung Jiwa by Okky Madasari? This study uses Qualitative Descriptive Research. The data in this study is the text in the novel Pasung Jiwa by Okky Madasari, and the data source used is the novel Pasung Jiwa. The data collection technique used is the reading and recording technique. The results obtained are (1) The Id analysis of the character